The persistent attractions of low-tech: Challenging the efficiency paradigm of forensic technology - Vestad, Maja (International journal of police science & management, 2024)
The promise of efficiency is a catalyst for technological development in forensic science and crime scene investigation practices. Crime scene investigators aim to locate and document every potential trace for evidence and investigate crime scenes as quickly, accurately and objectively as possible. This narrative suggests that performance leads the police to adopt new efficient technologies. But to what extent is this narrative reflective of actual practices? Through examining how crime scene investigators use existing technologies in practice, i.e. traditional or ‘low-tech’ methods and tools such as DNA detection dogs and manual documentation tools, this article shows that the use of low-tech persists even under the pressure to perform and achieve. The study finds that low-tech remains attractive as a less-restraining alternative to digital and high-tech solutions. It is also contrast to, integrated with or necessary in co-existence with high-tech for crime scene investigations practices to function. The study draws on fieldwork conducted at police stations in Norway, including interviews and participatory observation of investigations in practice, to discuss the persistent attractions of low-tech and what the implications are for research into policing and technology.